Peripheral Ossifying Fibroma in Infant: A Case Report - Syed Mohammed Yaseen; Ravindranath Acharya; Satish Yadav (Journal of Dental Problems and Solutions - Peertechz Publications, 2015)
Peripheral ossifying fibroma is a relatively common gingival growth of reactive rather than neoplastic in nature. Clinically differentiating one from the other as a specific lesion is often difficult and requires histopathology examination. It predominantly affects adolescents and young adults, but rarely seen in infants. We report here a clinical case of peripheral ossifying fibroma in a 3 month old infant .clinical and histopathological features along with etiopathogenesis and differential diagnosis are also discussed.